A Distributed Fault/Intrusion-Tolerant Sensor Data Storage Scheme Based on Network Coding and Homomorphic Fingerprinting - Zeng, Rongfei; Jiang, Yixin; Lin, Chuang; Fan, Yanfei; Shen, Xuemin (IEEE transactions on parallel and distributed systems, 2012)
Recently, distributed data storage has gained increasing popularity for reliable access to data through redundancy spread over unreliable nodes in wireless sensor networks (WSNs). However, without any protection to guarantee the data integrity and availability, the reliable data storage cannot be achieved since sensor nodes are prone to various failures, and attackers may compromise sensor nodes to pollute or destroy the stored data. Therefore, how to design a robust sensor data storage scheme to efficiently guarantee the data integrity and availability becomes a critical issue for distributed sensor storage networks. In this paper, we propose a distributed fault/intrusion-tolerant data storage scheme based on network coding and homomorphic fingerprinting in volatile WSNs environments. For high data availability, the proposed scheme uses network coding to encode the source data and distribute encoded fragments with original data pieces. With secure, compact, and efficient homomorphic fingerprinting, our scheme can fast locate incorrect fragments and then initialize data maintenance. Extensive theoretical analysis and simulative results demonstrate the efficacy and efficiency of the proposed scheme.